Historiozofia alternatywna w prozie Wiktora Pielewina. Na przykładzie powieści „Empire V” i „Batman Apollo” - Jaworski, Mateusz (Studia Rossica Posnaniensia, 2016)
The aim of the paper is an attempt to interpret Viktor Pelevin’s Empire V and Batman Apollo in the context of alternative historiosophy. The author of the article tries to interpret the notion of history within the aforementioned works by Pelevin, who perceives human history as a well-organized machine which imposes suffering on the weak.